MERAWAT LINGKUNGAN DENGAN TRADISI ISLAM - Nasruddin Anshoriy (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2012)
This article aims to reveal the relation that exists in the nature, therelation among God, man, and nature. This relation could make peoplerealize to preserve the nature. The Islam concept of tawbah, ama>nah, andakhi>rah can be explored and related to the environmental preservation.This article is a field note of the writer on saving the earth. The movementon environmental preservation which is famous as green spirit isseriously needed to save human from extinction. This article shows away to encourage people to think about the environment’s role on buildinga ‘God city’ as stated by philosophers. This is a kind of challenge forMuslims to look after their environment with pure soul.